2020
DOI: 10.1007/s12072-020-10026-0
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of antiviral therapy for HBV in different trimesters of pregnancy: systematic review and network meta-analysis

Abstract: Background Several antiviral agents licenced for blocking mother-to-child transmission (MTCT) of HBV, but their relative efficacy beginning from different trimesters has scarce been evaluated. We aimed to conduct a network meta-analysis to statistically differ the efficacy and safety of each antiviral agents initiating on different timings in preventing mother-to-infant transmission of HBV. Methods Studies were included from PubMed, EMBASE, Web of Science, and Cochrane databases through July 1, 2019. Eligible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…Numerous studies have emerged in recent years that favor the use of tenofovir disoproxil fumarate (TDF) because of its high efficacy and safety profile in addition to its high barrier to resistance (Table 4). [6][7][8][9][10][11][12] Patients who become pregnant while already maintained on HBV treatment should be assessed for both the appropriateness of the drug therapy and their response to treatment. Patients should be continued on HBV antiviral therapy (AVT) throughout the pregnancy and after delivery in the long term.…”
Section: Hepatitis B Virusmentioning
confidence: 99%
“…Numerous studies have emerged in recent years that favor the use of tenofovir disoproxil fumarate (TDF) because of its high efficacy and safety profile in addition to its high barrier to resistance (Table 4). [6][7][8][9][10][11][12] Patients who become pregnant while already maintained on HBV treatment should be assessed for both the appropriateness of the drug therapy and their response to treatment. Patients should be continued on HBV antiviral therapy (AVT) throughout the pregnancy and after delivery in the long term.…”
Section: Hepatitis B Virusmentioning
confidence: 99%
“…A Bayesian network meta-analysis and system review showed that the risk of MTCT decreased significantly in pregnant women accepting intervention before 28 weeks of gestation, as compared to those initiating after 28 weeks (relative risk: 0.019, (0.00034-0.19)). 36 Additionally, the efficacy and safety of antiviral therapy initiated from 24 weeks of gestation have been identified in cohort studies and case-control studies. 10 , 11 , 31 , 37 , 38 Therefore, pregnant women with high HBV DNA levels (>2×10 5 IU/mL) are recommended to initiate antiviral intervention at 24-28 weeks of gestation.…”
Section: Recommendationsmentioning
confidence: 99%
“…Systematic review and meta-analysis report lamivudine, telbivudine and tenofovir disoproxil fumarate (tenofovir) provided in the third trimester can interrupt MTCT of HBV in hepatitis B e antigen (HBeAg) positive women with high HBV DNA > 10 6 IU/mL [13]. Recent meta-analysis suggests better prevention of MTCT with telbivudine and tenofovir, and by initiation of antivirals before the third trimester [13]. However the reduction of HBV DNA is highly dependent on starting viraemia and weeks of treatment with tenofovir.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence from HIV that antivirals are safe and effective in prevention of MTCT in RLS in Africa and Asia [ 9 12 ]. Systematic review and meta-analysis report lamivudine, telbivudine and tenofovir disoproxil fumarate (tenofovir) provided in the third trimester can interrupt MTCT of HBV in hepatitis B e antigen (HBeAg) positive women with high HBV DNA > 10 6 IU/mL [ 13 ]. Recent meta-analysis suggests better prevention of MTCT with telbivudine and tenofovir, and by initiation of antivirals before the third trimester [ 13 ].…”
Section: Introductionmentioning
confidence: 99%